PARADIGMA PEMIKIRAN PENDIDIKAN KH. AHMAD DAHLAN - Suripto, Suripto (ILJ: Islamic Learning Journal, 2023)
Education is a really important matter. many well-known figures, one of which is KH. Ahmad Dahlan. this research is library research with documentary data collection method, and analysis with content analysis. Basic paradigm of KH. Ahmad Dahlan’s concept of educational thought were formed an educational process that was educated by his family, teachers up to he studied in Makkah, and was inspired by his reading leturature books, specially from  the thought books of Muhammad Abduh and Jamludin Al-Afghani. Starting from his deep understanding of Al-Qur’an and Al-Hadits Which is contextualized with empirical ralitythrough a philoshopical approach, the construction of the paradigm of Islamic education thought KH. Ahmad Dahlan was placed on the formulation of th concept educational goal. To realize these educational goal, KH Ahmad Dahlan developed a school system educational with combining two educational models, namely the madrasa system and school.